2018
DOI: 10.4314/gmj.v51i4.11
|View full text |Cite
|
Sign up to set email alerts
|

Hydatid cyst of the orbit in a young Nigerian female: a case report

Abstract: Objective: To report an unusual case of orbital hydatid cyst successfully managed by surgical excision.Case report: A 33-year-old female presented with gradual protrusion of the left eye associated with poor vision, cosmetic embarrassment and watering. She had excision biopsy of an encapsulated cystic lesion with cheesy tissue and serous content. Orbital hydatid cyst due to echinococcosis was confirmed at histopathological examination of the excised tissue. She subsequently became pregnant hence, could not und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 11 publications
2
17
0
2
Order By: Relevance
“…In humans, studies have demonstrated 0%-3% CE prevalence in endemic regions (Assefa et al, 2015;Barclay et al, 2013;Klungsøyr, Courtright, & Hendrikson, 1993;Magambo, Hall, Zeyle, & Wachira, 1996;Magambo, Zeyhle, & Wachira, 1998;Shambesh et al, 1999) and <1% in non-endemic regions (Dada, 1980;Sixl, Rosegger, Schneeweiss, Withalm, & Schuhmann, 1987). A major challenge of CE infection in humans is the frequent misdiagnosis due to the covert clinical presentation and chronic nature of Echinococcus infection (Fasina & Ogun, 2017;Kassa, Yeshi, Abraha, & Gebremariam, 2014). Therefore, a high index of suspicion in patients visiting hospitals with unusual presentations has been suggested to guide towards identifying CE infection (Kassa et al, 2014).…”
Section: Economic and Public Health Importancementioning
confidence: 99%
“…In humans, studies have demonstrated 0%-3% CE prevalence in endemic regions (Assefa et al, 2015;Barclay et al, 2013;Klungsøyr, Courtright, & Hendrikson, 1993;Magambo, Hall, Zeyle, & Wachira, 1996;Magambo, Zeyhle, & Wachira, 1998;Shambesh et al, 1999) and <1% in non-endemic regions (Dada, 1980;Sixl, Rosegger, Schneeweiss, Withalm, & Schuhmann, 1987). A major challenge of CE infection in humans is the frequent misdiagnosis due to the covert clinical presentation and chronic nature of Echinococcus infection (Fasina & Ogun, 2017;Kassa, Yeshi, Abraha, & Gebremariam, 2014). Therefore, a high index of suspicion in patients visiting hospitals with unusual presentations has been suggested to guide towards identifying CE infection (Kassa et al, 2014).…”
Section: Economic and Public Health Importancementioning
confidence: 99%
“…Common symptoms include unilateral, progressive proptosis (nontender or with mild pain/discomfort), restricted ocular motility, visual changes, and conjunctival chemosis 93,94,97 . In chronic cases, there may be compressive optic neuropathy with choroidal folds 98 . A thorough history may uncover useful diagnostic clues, such as previous infection with E. granulosus elsewhere in the body, positive serology, or a history of travel to endemic areas, particularly rural locations with exposure to dogs and/or livestock 93,96,98 …”
Section: Infectious and Inflammatory Cystsmentioning
confidence: 99%
“…При использовании орбитальных доступов часто в качестве интраоперационного осложнения наблюдались разрывы кисты [6,27]. Это осложнение не только может приводить к диссеминации процесса и рецидивам, но и к развитию анафилактического шока.…”
Section: клинический случайunclassified
“…Известно также, что неадекватная противопаразитарная терапия может давать временное улучшение (уменьшение полостей эхинококковой кисты, уплотнение ее оболочек) с последующим развитием рецидива [26]. Пациенты с эхинококкозом глазницы обращаются за медицинской помощью, как правило, когда сформировавшийся патологический процесс требует быстрого хирургического решения и не оставляет альтернативы для длительной консервативной терапии [27].…”
unclassified